Maintaining a Minority Sport: Cricket in Post-Colonial Hong Kong. Issue 11 (23rd July 2016) - Bridges, Brian
Abstract: Cricket was one of the main sports that typified British imperial cultural exports, but in the colony of Hong Kong it remained largely a pursuit with limited appeal beyond expatriates and South Asian residents. After 1997, the cricket community did receive better financial and administrative support, but a consistent policy to promote the sport was lacking. Hong Kong cricket officials have become increasingly aware of the need to extend the sport more effectively to the Chinese community and, ultimately, to mainland China itself. As Hong Kong and its citizens face increasingly contentious debates over individual and collective identity, this article considers the sociocultural challenges facing a sport whose historical development and current realities are steeped in colonial images.